Pseudotail with closed neural tube defect and neurogenic bladder masquerading as posterior urethral valve: a case report - Ram Jeewan Singh; Md Mokarram Ali; Amit Kumar; Rashi Rashi; Amit Kumar Sinha; Bindey Kumar (SpringerOpen, 2021)
Abstract Background Pseudotail with occult spinal dysraphism with neurological deficit is a rare phenomenon. Ignoring pseudotail as sign of occult spinal dysraphism may lead to catastrophe in diagnosis and further management. Case presentation We are reporting a case of a 30-month-old male child who presented with a tail-like structure at lower back and dribbling of urine since birth. On initial evaluation at some other hospital, he was misdiagnosed as posterior urethral valve and underwent fulguration of valve. However, dribbling of urine persisted after initial procedure. On evaluation at our center, he was found to have pseudotail with occult spinal dysraphism and neurogenic bladder. Conclusion Pseudotail with occult spinal dysraphism with neurological deficit is a rare phenomenon. Neurogenic bladder in such case can be misdiagnosed as posterior urethral valve. So, neurogenic bladder with pseudotail should be evaluated cautiously to avoid misdiagnosis and mismanagement.